ART, TECHNOLOGY, AND SOCIETY: EMERGING INTERSECTIONS IN VISUAL AND PERFORMING ARTS RESEARCH - Basa, Murali; Çağlar, Bayram; Prajapati, Nirpat Prasad; Karwande, Vijay Suresh; Chakravorty, Noveena (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This special issue of ShodhKosh: Journal of Visual and Performing Arts examines how digital technologies, artificial intelligence, and interdisciplinary research are reshaping contemporary artistic practice. The articles explore AI‑driven creativity, ethical questions of authorship, cultural analytics, and data‑based insights into aesthetic trends. Studies on virtual performance spaces, augmented reality, immersive design, and digital archiving highlight the transformation of artistic environments. The issue also emphasizes the therapeutic role of music, movement, and mindfulness in enhancing well‑being. Additional contributions address social change, environmental narratives, and emerging cyber‑physical art systems. Together, these works underscore the arts Issue Editor: Dr. Murali Basa Assistant Professor, Department of Performing Arts, Assam University, Silchar, India Email: murali.basa@aus.ac.in / muralibasa@gmail.com Dr. Bayram ÇAĞLAR Lecturer, Kocaeli University Ömer İsmet Uzunyol Vocational School, Department of Auditory Techniques and Media Production, Turkey Email: bcaglar@kocaeli.edu.tr Dr. Nirpat Prasad Prajapati Head, Department of Hindi & Research Director, Institute for Excellence in Higher Education (IEHE), Bhopal, Madhya Pradesh, India Email: drnirpatprasadprajapari@gmail.com Dr. Vijay Suresh Karwande, Assistant Professor, Department of Computer Engineering, Sandip Institute of Technology and Research Centre, Nashik, India Email: vijayskarwande@gmail.com Dr. Noveena Chakravorty Associate Professor, Department of Media and Studies, School of Media and Communication, Adamas University, Kolkata, West Bengal, India Email: noveena.jimmc@gmail.com